2014
DOI: 10.4161/nucl.29229
|View full text |Cite
|
Sign up to set email alerts
|

Coilin is rapidly recruited to UVA-induced DNA lesions and γ-radiation affects localized movement of Cajal bodies

Abstract: (2014) Coilin is rapidly recruited to UVA-induced DNA lesions and γ-radiation affects localized movement of Cajal bodies, Nucleus, 5:3,[269][270][271][272][273][274][275][276][277]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 35 publications
3
23
0
Order By: Relevance
“…BRCA1 appeared at DNA lesions between 20 and 80 min after local micro‐irradiation (Figure A, an interval of observation up to 50 min was normalised by shown for all proteins). Intriguingly, the most rapid accumulation at DNA lesions was observed for GFP‐tagged coilin (Bártová et al., ), BMI1 (see Šustáčková et al., ); here we showed accumulation of endogenous BMI1 and RFP‐tagged PCNA (Figure A).…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…BRCA1 appeared at DNA lesions between 20 and 80 min after local micro‐irradiation (Figure A, an interval of observation up to 50 min was normalised by shown for all proteins). Intriguingly, the most rapid accumulation at DNA lesions was observed for GFP‐tagged coilin (Bártová et al., ), BMI1 (see Šustáčková et al., ); here we showed accumulation of endogenous BMI1 and RFP‐tagged PCNA (Figure A).…”
Section: Resultssupporting
confidence: 69%
“…() and Bártová et al. (). Here, we compared recruitment of BMI1 and coilin to DNA lesions with the well‐known DNA damage‐related protein, BRCA1, which appears rapidly at DNA damage sites (Scully et al., ).…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies made similar conclusions related to the movement of the nuclear domain, for example, different classes of PML bodies or Cajal bodies (CBs) which are highly mobile in non-irradiated cells. 27,29,33 Moreover, we recently demonstrated that local CB motion decreases after g-irradiation, which is in agreement with data that radiation induces changes in nuclear domain trajectories (compare 32 with Fig. 2Bc, white arrows).…”
Section: Discussionsupporting
confidence: 78%
“…2A-D, 4A, 4B, or Ref. 14,32 ). In this study, we analyzed the GFP-UBF1-positive regions of nucleoli after exposure to UVA or g-radiation.…”
Section: Discussionmentioning
confidence: 99%
“…18 The interaction between coilin and WRAP53 could also explain why coilin is found at sites of DNA damage, and CBs are sensitive to UV irradiation. 55,56 While coilin function during DNA repair is unclear, WRAP53 was recently shown to be critical for DNA double-strand break repair. 57 Independent work found coilin associated with DNA repair factor Ku.…”
Section: Coilin Historymentioning
confidence: 99%